2022
DOI: 10.1039/d1se02067f
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the selectivity of hydrocarbons during the Kolbe electrolysis of biomass-derived short-chain carboxylic acids by anionic surfactants

Abstract: Different mechanisms of selective electrochemical decarboxylation of acetic acid and butyric acid in aqueous solution and at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…It can also be noted that by keeping [PA] 0 at 2 M, butane production remained inhibited and ethane production remained negligible, for the same reasons discussed in the previous section. For all the current densities studied, the anode potentials were measured to be within 2.6 and 4.4 V vs. RHE, which is consistent with the literature 17,31–33 (see ESI†). Interestingly, within the range of current densities evaluated, the half-cell potential appeared to slightly decrease with increasing current between 20 and 45 mA cm −2 , which can be attributed to an increase in the electrolyte temperature at higher current density due to the increased ohmic losses and leading to a reduction of reaction overpotentials.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…It can also be noted that by keeping [PA] 0 at 2 M, butane production remained inhibited and ethane production remained negligible, for the same reasons discussed in the previous section. For all the current densities studied, the anode potentials were measured to be within 2.6 and 4.4 V vs. RHE, which is consistent with the literature 17,31–33 (see ESI†). Interestingly, within the range of current densities evaluated, the half-cell potential appeared to slightly decrease with increasing current between 20 and 45 mA cm −2 , which can be attributed to an increase in the electrolyte temperature at higher current density due to the increased ohmic losses and leading to a reduction of reaction overpotentials.…”
Section: Resultssupporting
confidence: 87%
“…Secondly, it has also been demonstrated that the shorter the chain of the carboxylic acid, the higher the yield towards the two electron reactions (non-Kolbe and Hoefer-Moest product) over the single-electron reaction (Kolbe dimerization and disproportionation) which might be due to the relatively lower stabilities of the alkyl radical in shorter chains. 32,33 Even at high concentrations of the substrate, these two factors prevent the formation of butane. It remains unclear why the disproportionation reaction is observed and the dimerization reaction is not.…”
Section: Effect Of Initial Substrate Concentrationmentioning
confidence: 99%
“…Note that there is a possibility that reactions proceeding at a cathode change depending on cathode materials, and the cathodic reaction can affect the yield of the target compound. Notably, our electrochemical protocol did not require precious metals such as Pt electrodes, which are generally used in the Kolbe electrolysis (entry 6) [47–49] . Electrosynthesis conducted for two and three hours afforded 2 in 40 % and 49 % yields, respectively (entries 10 and 11).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, our electrochemical protocol did not require precious metals such as Pt electrodes, which are generally used in the Kolbe electrolysis (entry 6). [47][48][49] Electrosynthesis conducted for two and three hours afforded 2 in 40 % and 49 % yields, respectively (entries 10 and 11). We also tried the reactions with increased amount of methanol (10 eq.)…”
Section: Reaction Optimizationmentioning
confidence: 99%
“…For instance, the phenomenon is commonly observed in Kolbe electrolysis where the dimerization of alkyl radicals benefits from a high concentration of the starting materials. [55][56][57] For the second experiment, the radical inhibitor butylated hydroxytoluene was added into the system using Ni-CP electrode at the optimized conditions, the reaction still proceeded smoothly with up to 90% conversion. Based on these observations, it is unlikely that the reaction system proceeded via a free radical mechanism.…”
Section: Mechanism Discussionmentioning
confidence: 99%